The EcoGothic and Contemporary Sri Lankan English Literature: Reading Ecophobia in Patricia Weerakoon’s Empire’s Children and Roma Tearne’s Mosquito - Daimari, Esther (SARE: Southeast Asian Review of English, 2022)
This paper explores contemporary Sri Lankan fiction as expressions and experiments in postcolonial EcoGothic writing by highlighting an intense relationship between ecology and place. By examining the novels of three contemporary Sri Lankan writers – Roma Tearne’s Mosquito, Michael Ondaatje’s Anil’s Ghost, and Patricia Weerakoon’s Empire’s Children, the article examines how certain landscape tropes such as the sea, the forest, ruins, caves, and tea plantations are shaped by the writers as gothic spaces to share their ecological concerns. The eerie plantations in Empire’s Children and the fecund forest, groves and the sea in Mosquito, and the caves and mass graves in Anil’s Ghosts allude to traumas related to postcoloniality, war, and military territorialization. Building upon theories of landscape, ecocriticism, and more specifically, the EcoGothic, the article draws upon works by Sharae Deckard and others to suggest how in these novels, the landscape is not just a setting for the stories but palimpsests of multiple histories of violence on both the people and the environment. The article examines how the novel enacts violence and spatial disorientation, closely connected with the gothic genre, suggesting Anglophone contemporary Sri Lankan fiction writers’ recurrent exploration of gothic and ecology in their works.